2015
DOI: 10.1007/s11938-014-0043-6
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Esophageal Strictures: What To Do When Dilation Fails

Abstract: Opinion statementBenign esophageal strictures arise from a diversity of causes, for example esophagogastric reflux, esophageal resection, radiation therapy, ablative therapy, or the ingestion of a corrosive substance. Most strictures can be treated successfully with endoscopic dilation using bougies or balloons, with only a few complications. Nonetheless, approximately one third of patients develop recurrent symptoms after dilation within the first year. The majority of these patients are managed with repeat d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
91
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 70 publications
1
91
0
4
Order By: Relevance
“…It supports previous data that also exposed an increasing number of dilations during the first year as a predictive factor for non-responsive PES [7] and severely narrowed strictures as a challenging situation [2,8]. Although other characteristics with recognized association to difficult treatment in this setting of aetiology, as stricture length, complexity, and location [8,9], would add value to this analysis if available in a larger population sample. Interestingly, refractory strictures did not present as a worse condition in this population and the authors suggested that these patients may still benefit from endoscopic therapy.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…It supports previous data that also exposed an increasing number of dilations during the first year as a predictive factor for non-responsive PES [7] and severely narrowed strictures as a challenging situation [2,8]. Although other characteristics with recognized association to difficult treatment in this setting of aetiology, as stricture length, complexity, and location [8,9], would add value to this analysis if available in a larger population sample. Interestingly, refractory strictures did not present as a worse condition in this population and the authors suggested that these patients may still benefit from endoscopic therapy.…”
supporting
confidence: 86%
“…The subjective "improvement" of dysphagia included in their definition of efficacy may contribute to this. However, it is known that the long-term outcome of endoscopic treatment for refractory benign esophageal strictures is time-consuming and disappointing with less than one-third of the patients achieving a resolution of the dysphagia, even when other techniques such as steroid injections, incisional therapy, stent placement, or self-bouginage are added to dilation therapy [5,9]. Patients and physicians should realize that repeated sessions (with inherent risks) and visits to the hospital will be needed for a possible effective treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…41 The efficacy of intralesional triamcinolone injection in peptic strictures has been shown by Ramage and colleagues 42 in a randomized double-blind placebo-controlled trial. 42 In this study, 2 (13%, 95% confidence interval [CI] 4%-38%) of 15 patients in the steroid group and 9 (60%, 95% CI 36%-80%) of 15 in the sham group required repeat dilation (P 5 .021).…”
Section: Intralesional Steroid Injectionmentioning
confidence: 95%
“…In recurrent cases may need additional endoscopic treatment options such as incisional methods, stent placement or a combination of these. Rarely, in failure of these methods surgical intervention is used 1,6 . Serious complications such as perforation even death may occur during endoscopic dilatation of benign esophageal strictures 7,8 .…”
Section: Introductionmentioning
confidence: 99%